Innovation of Learning Management in Madrasah Level - Zamroni, Zamroni (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The presence of Islamic education i.e. madrasah has significantly contributed to the live of public citizen in Indonesia. Therefore, the existence of madrasah education develops in accordance with the needs and demands of society today as well as it be able to adjust the existence of the industrial revolution 4.0. The development madrasah education must be done by increasing the quality of human resources, redesigning curriculum development and managing the quality of learning. In this context, as an effort to achieve the above educational goals, new breakthroughs in the field of learning are needed i.e. continuous quality improvement by carrying out various approaches, especially in the field of learning management innovation in order to drive the Islamic education as a central for excellence where the students are able to compete in the midst of the 4.0 industrial revolution era. The existence of learning management essentially aims to build and develop the full potential of learners, and these efforts can only be made if all learning activities are programmed in accordance with the needs of students, parents, and society expectations. Therefore, at the practical level, learning activities are understood to be able to run effectively and efficiently if all of the above activities start from the managerial process, through the learning planning process; learning management; management of students management of quality human resources or professionalism of teachers; development of learning activities and the process of evaluating good learning.